2010
DOI: 10.1590/s1516-35982010001200006
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter yield and nutritional value of Marandu grass under nitrogen fertilization and irrigation in cerrado in São Paulo

Abstract: -The aim of this study was to evaluate dry matter yield and nutritional value of palisade grass (Brachiaria brizantha cv. Marandu) using nitrogen doses and sprinkler irrigation in two periods of the year, aiming at reducing seasonality of forage production. It was used a randomized block design in a split-plot scheme, with five doses of nitrogen (0, 50, 100, 150, and 200 kg/ha/cut), and the sub-plots were defined by the seasons of the year (wet and dry season), with and without irrigation. During the wet seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 6 publications
4
14
1
10
Order By: Relevance
“…Produtividades máximas de forragem foram obtidas com aplicações de lâminas de 267 e 269 mm para o outono e o inverno, respectivamente. Tal comportamento de resposta em forrageiras foi também observado por ALENCAR et al (2009b), LOPES et al (2014) e DUPAS et al (2010.…”
Section: Resultsunclassified
“…Produtividades máximas de forragem foram obtidas com aplicações de lâminas de 267 e 269 mm para o outono e o inverno, respectivamente. Tal comportamento de resposta em forrageiras foi também observado por ALENCAR et al (2009b), LOPES et al (2014) e DUPAS et al (2010.…”
Section: Resultsunclassified
“…The results obtained are in agreement with those found by Corrêa et al (2007), who observed an increase in DMY according to the increase of N doses (0, 25, 50, 100 and 200 kg ha -1 per cut). A number of studies have reported the positive effect of nitrogen fertilization on pasture (Benett et al, 2008, Dupas et al, 2010, Batista et al, 2014. However, Fernandes et al (2015) suggested that it is possible that the soil can supply the N requirement of the forage grasses depending on the soil type and management of the area, reaching a good productive level.…”
Section: Discussionmentioning
confidence: 99%
“…in the non-irrigated experiment, that is, with no statistically significant difference [37]. In the dry season, the average DM yields were 8.1 t ha −1 in the irrigated treatment and 4.4 t ha −1 under non-irrigated treatment.…”
Section: Right Timementioning
confidence: 79%